Analysis, monitoring, and mitigation of power quality disturbances in a distributed generation system - Ravi, T.; Sathish Kumar, K. (Frontiers in Energy Research, 2022)
Despite the numerous benefits of distributed generation (DG), such as reliable energy supply and environmental friendliness, there are a number of challenges associated with integrating DG with the grid. In the field of DG, the complication of power quality (PQ) is a major technical challenge. Custom power devices (CPDs) are used in the distribution system to solve complications. This study presents different PQ disturbances (PQDs), monitoring techniques, and fundamental standards. Furthermore, with the widespread literature, the study critically reviews different PQ mitigation techniques such as distribution static compensator (DSTATCOM), dynamic voltage restorer (DVR), unified power quality conditioner (UPQC), and uninterruptable power supply (UPS). The present research work is not only limited to surveying the existing techniques but also analyzing the performance of UPQC using the ANFIS controller. Overall, this study is intended to provide researchers working on improving PQ in the distribution system with a valuable resource that will aid them in enriching their research.